A blueprint for the interpretation of GST Act 1985 with reference to Privy Council and Supreme Court decisions - Lu, Yunting (Auckland University of Technology, 2010)
GST is a substantial revenue raiser for New Zealand. It has been internationally acclaimed and adopted by other countries. The framework for the tax is prescribed by the Goods and Services Tax Act 1985 (“the Act”). Under the Act, GST is charged on a supply of goods and services made in New Zealand on or after 1 October 1986 by a registered person in the course or furtherance of a taxable activity which is not an exempt supply.2 Given the fiscal significance of GST, the Act is a significant piece of legislation. How is this significant legislation to be read and applied? This paper interprets some of the leading court decisions. It is, of course, the role of the courts to interpret and apply the Act. The higher the court the more authoritative the decision, and the more likely its reasoning is to be applied in subsequent cases. The decisions of the highest court – the Privy Council and, more recently, the Supreme Court – should therefore be accorded great weight when interpreting GST law. The paper therefore analyses threshold decisions of the Privy Council and the Supreme Court on the Act.
Keywords: Interpretation; GST Act 1985